ATTEMPTED PREPARATION OF N-SUBSTITUTED DIPHENYLCYCLOPROPENEIMINE N-OXIDE (Journal of Sciences, Islamic Republic of Iran)
The reaction of diphenylcyclopropenone with several N-substituted hydroxylamine and primary amines are investigated. Most of these reactions led to ring opened or ring enlarged products, instead of the desired N-Oxide or imine. The reaction of cyclopropeneimine with peracid-another possible route to N-substituted cyclopropeneimine N-Oxide is studied. Most of the unexpected products are identified and herein reported